Debt issues in Africa: Thinking beyond the HIPC initiative to solving structural problems - Alemayehu Geda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper attempts to answer the following question: If the HIPC Initiative is fully successful and managed to write-off all debt that is owed by Africa, will the debt problem be over? The answer is `no'. This pessimist answer is arrived at by examining the historical origin of African debt and the structural problems the continent is confronted with. The literature about the origins of the African debt crisis lists a number of factors as its cause. The oil price shocks of 1973-74 and 1978-79, the expansion of the Eurodollar, a rise in public expenditure by African governments following rising commodity prices in early 1970s, the recession in industrial countries and the subsequent commodity price fall, and a rise in real world interest rate are usually mentioned as major factors. Surprisingly, almost all the literature starts its analysis either in the early 1970s or, at best, after independence in 1960s. The main argument in this paper is that one has to go beyond this period not only to adequately explain the current debt crisis but also to propose its possible solution. The conclusion that emerges from such analysis is that the African debt problem is essentially a trade problem. Thus, long-run solution to debt points to the importance of addressing trade and trade related structural problems in the continent. – debt ; trade ; Africa
Keywords: F1; F34; F35; N77; E44; 330; Auslandsverschuldung; Schuldenerlass; Wirtschaftliche Anpassung; Afrika